ANALISIS PRINSIP DAN INSTRUMEN DALAM EVALUASI PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Bagas Aditya Achmad; Nila Hani Awalia (CV. Denasya Smart Publisher, 2024)
Learning evaluation is very important in education to determine the success of the teaching and learning process. This research aims to analyze the concepts and principles of mathematics learning evaluation and review the instruments used. The research method used is a literature study of the latest sources regarding learning evaluation. The research results show that evaluation aims to assess and provide feedback on the learning process, where principles such as continuity, comprehensiveness and fairness must be taken into account. There are two main types of instruments, namely tests and non-tests, where non-tests are suitable for assessing affective and psychomotor domains. This research is useful for understanding the concepts and methods of learning evaluation so that the learning process can continue to be refined.